THE EFFECTIVENESS OF ADDING ORGANIC INGREDIENTS OF PURPLE SWEET POTATO EXTRACT TO THE GROWTH OF IN VITRO CUTTINGS OF Macodes petola ORCHIDS - Nurtriyani, Gani (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTThis study aims to determine the effect of some medium concentration of purple sweet potato (Ipomoea batatas L) extract on growth of Macodes petola and to know the best of concentration on the growth of Macodes petola. The method used was Completely Random Design consisted of 6 treatments, 4 replications and each replication consist of 2 plant samples. Purple sweet potato extract concentration is as follows: without the addition of purple sweet potato extract, 75 ml/l, 150 ml/l, 225 ml/l, 300 ml/l and 375 ml/l. Observed parameters are the number of leaves, number of roots, the number of shoots, time when shoots appear and when roots arise. The results showed that the sweet potato extract give the same result without additions of the sweet potato extract for the period of shoot emergence and time to root emergence time to. Without additions of the sweet potato extract more effective for the number of leaves, the number of roots and the number of shoots.Keywords: Extract Of Purple Sweet Potato (Ipomoea Batatas L), Orchids Macodes petola, Tissue Culture.